Identification of Paracoccidioides brasiliensis in adrenal glands biopsies of two patients with paracoccidioidomycosis and adrenal insufficiency (2009)
ABSTRACT : The authors report two cases of adrenal insufficiency secondary to infiltration of the adrenal glands by Paracoccidioides brasiliensis. The first patient had been treated for a chronic multifocal form of paracoccidiodomycosis 11 years ago. The diagnosis of the mycosis was done simultaneous with that of the adrenal insufficiency in the second patient. In both patients the diagnosis was done by direct visualization of fungus in adrenal biopsies. They were treated with hormonal supplements and itraconazol by 12 and six months, without relapses during the follow-up period.